ANALISIS PERBEDAAN TINGKAT KEPUASAN PELANGGAN ANTARA PENGGUNA GOJEK DAN GRAB DI LINGKUNGAN UNTAG SAMARINDA - Danna Solihin; Nurfitriani Nurfitriani; Andi Indrawati; Eka Yudhyani (Jurnal GeoEkonomi, 2024)
Online transportation is a menas of transportation that uses technological advances based on applications and allows orders and payments to be made by the application at the same time. The transportation industry looks profitable, examples of companies in the transportation industry that are developing rapidly are Gojek, Grab and Maxim. However, the most dominant rivalry in the transportation industry is between Gojek and Grab. This research purpose to compare the level of customer satisfaction between Gojek and Grab users. This research uses quantitative methods with primary data source collect through distributing questionnaires to Gojek and Grab users in Samarinda City, East Kalimantan. The results of the research after conducting and distributing the questionnaire that was created, we concluded that the comparison between Gojek and Grab doesn’t have a significant difference, because both applications have almost the same features and the average user only uses one of the two applications.